Analysis of Mental Workload in Online Shopping: Are Augmented and Virtual Reality Consistent? - Zhao, Xiaojun; Shi, Changxiu; You, Xuqun; Zong, Chenming (Frontiers in Psychology, 2017)
A market research company (Nielsen) reported that consumers in the Asia-Pacific region have become the most active group in online shopping. Focusing on augmented reality (AR), which is one of three major techniques used to change the method of shopping in the future, this study used a mixed design to discuss the influences of the method of online shopping, user gender, cognitive style, product value, and sensory channel on mental workload in virtual reality and augmented reality situations. The results showed that males’ mental workloads were significantly higher than females’. For males, high-value products’ mental workload was significantly higher than that of low-value products. In the VR situation, the visual mental workload of field-independent and field-dependent consumers showed a significant difference, but the difference was reduced under audio-visual conditions. In the AR situation, the visual mental workload of field-independent and field-dependent consumers showed a significant difference, but the difference increased under audio-visual conditions. This study provided a psychological study of online shopping with augmented and virtual reality technology with applications in the future.